PERENCANAAN JEMBATAN PRATEGANG KALI SURU PEMALANG - Achmad Santosa; Sugiyanto Sugiyanto; Y.I. Wicaksono; Indrastono Dwi Atmono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Suru bridge is located in the village of Suru, Bantar bolang, Pemalang linking local and regional Кesesi Bantar Bolang route its span 144 meters above the river suru. Suru bridge replacement is based on conditions that exceed the design life of the bridge, steel truss bridge already rusty and the effective width of the bridge that does not meet the standards to serve the transportation needs. On the condition of the bridge was originally designed using the bridge structure type steel frame, then in this final project design for the replacement bridge suru use this type of prestressed concrete structures. At this early stage analysis exsisting conditions, the structural design of the upper structure and sub structure as well as the calculation of the Budget Plan (RAB). Planning the structure take into account the burden that might occur that burden alone, additional dead load, traffic load, wind load and earthquake loads. In planning prosess carried out calculations using LRFD (Load and Resistance Factor Design) is then performed under the structural design with the initial steps do dimensioning abutments, pillars and foundation .For foundation wells are used caisson.